Testing Theories of Criminality and Victimization in Seattle, 1960-1990 - Miethe, Terance D. ([Verlag nicht ermittelbar], 1992)
The primary objective of this study was to test criminal opportunity theories of victimization and the collective benefits or harm resulting from citizen-based crime control activities. Other areas of investigation included crime displacement, "free-rider" effects (i.e., crimes occurring in conjunction with other crimes), and a multilevel analysis of victimization risks. Two types of data were gathered for this collection. First, census tract data were used to identify tracts that had not changed their physical boundaries since 1960. In addition, statistics were gathered from police reports for the same years. Variables for the census tract data (Part 1) include median family income in constant 1980 dollars, average number of persons per occupied housing unit, percent of labor force taking public transportation to work, percent of children under 18 living with both parents, and percent of civilian labor force that was female. Police report variables in Part 1 include rates per 100,000 population for homicide, rape, robbery, assault, residential burglary, and automobile theft. Secondly, during a telephone survey of Seattle residents conducted in 1990, respondents were asked a variety of questions about their experiences with crime and victimization. These data, presented in Part 2, cover burglaries, stolen property, physical assaults by strangers, vandalism, car thefts, type of neighborhood, type of home, security measures taken, and sociodemographic conditions. The unit of analysis for this data collection is housing units.